2021
DOI: 10.1177/01945998211061511
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Persistent Olfactory Disorders in Patients With COVID‐19: A Psychophysical Case‐Control Study With 1‐Year Follow‐up

Abstract: The purpose of this multicenter case-control study was to evaluate a group of patients at least 1 year after coronavirus disease 2019 (COVID-19) with Sniffin’ Sticks tests and to compare the results with a control population to quantify the potential bias introduced by the underlying prevalence of olfactory dysfunction (OD) in the general population. The study included 170 cases and 170 controls. In the COVID-19 group, 26.5% of cases had OD (anosmia in 4.7%, hyposmia in 21.8%) versus 3.5% in the control group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 27 publications
4
39
0
1
Order By: Relevance
“…Even before the pandemic, viral infections were the most frequent cause of persistent anosmia [47], yet the COVID-19 pandemic significantly increases the magnitude of this phenomenon. First, due to the very high number of patients with POD and PGD: up to 67% of all those who have had symptomatic COVID-19 [2][3][4][5][6][7][8][9][10][11][12][48][49][50][51][52][53]. Moreover, CD are also proving a frequent symptom in reinfections [13,14] and in COVID-19 in vaccinated individuals [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even before the pandemic, viral infections were the most frequent cause of persistent anosmia [47], yet the COVID-19 pandemic significantly increases the magnitude of this phenomenon. First, due to the very high number of patients with POD and PGD: up to 67% of all those who have had symptomatic COVID-19 [2][3][4][5][6][7][8][9][10][11][12][48][49][50][51][52][53]. Moreover, CD are also proving a frequent symptom in reinfections [13,14] and in COVID-19 in vaccinated individuals [15].…”
Section: Discussionmentioning
confidence: 99%
“…It has not yet been clarified what the frequency of persistent disturbances is in these groups of individuals, but if the prevalence recorded in cases of primary infection were confirmed, it would mean that this problem may not end with the immunization of the population. Second, the identification of the pathogenesis [54][55][56][57][58][59][60][61] and risk factors [2][3][4][5][6][7][8][9][10][11][12][62][63][64][65][66][67][68] for the development of persistent CD are in its infancy. For this reason, no effective therapies have yet been found for the prevention and treatment of COVID-19 related POD and PGD [69][70][71][72][73][74][75].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two very recent case–control studies have evaluated the persistence of smell and taste disorders at least one year after the onset of COVID-19 using psychophysical tests [ 51 , 52 ]. More specifically, Boscolo-Rizzo et al estimated that, overall, 58% of cases vs. 18% of controls had an olfactory or gustatory dysfunction, while 33% of cases self-reported a persistently altered sense of smell or taste at the time of the psychophysical evaluation [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, Boscolo-Rizzo et al estimated that, overall, 58% of cases vs. 18% of controls had an olfactory or gustatory dysfunction, while 33% of cases self-reported a persistently altered sense of smell or taste at the time of the psychophysical evaluation [ 51 ]. Vaira et al found that 26.5% of cases vs. 3.5% of controls had olfactory dysfunction on psychophysical tests, while 25.9% of patients self-reported some form of persistent olfactory loss, suggesting that qualitative and quantitative disturbances of smell may have similar clinical implications on the quality of life [ 52 ].…”
Section: Discussionmentioning
confidence: 99%